A települések infrastruktúra-fejlesztésének új feltételei és feladatai - Kőszegfalvi, György (Tér és Társadalom, 1989)
Issues related to the infrastructure of settlements are still very timely and of outstanding importance. Different conditions of socio-economic development have created a new situation and new tasks in settlement development and, as its integral and inseparable component, in the infrastructural supply of the population. A reinterpretation of the earlier concept is needed. A particularly decisive circumstance is to study the function and content of basic supply in a new approach, on the basis of a resolution adopted by the Parliament at its April session in 1985 on ,,Long-term tasks of spatial and settlement development". This has first of all a socio-political bearing from the aspect of strengthening the population-retaining capacity of rural areas and the development of living condition. Under the new conditions of infrastructural development, a new attitude is required in several questions. Questions like the following can be mentioned among them; what interests influence the infrastructural development of settlements: how can sectoral and regional interests be better co-ordinated; how can the complexity of infrastructural development be fostered; have norms and normative regulations any role in the organization of infrastructural supply? The present paper summarizes the results of several years of research into these questions, making use of an ample experince gained in settlements.